The Importance of Ischemia Modified Albumin in Chronic Hepatitis B and C - Senol, Arzu; Turkoglu, Semra (Galenos Yayincilik, 2021)
Objectives: In this study, it was aimed to investigate the ischemia modified albumin (IMA) and the IMA/albumin ratio (IMAR) and the relationship between these two parameters with fibrosis in patients with chronic hepatitis B (CHB), hepatitis B e antigen negative chronic infection (HBI) and chronic hepatitis C (CHC). Materials and Methods: This prospective study included 80 patients with CHB, 50 patients with HBI, 30 patients with CHC and 60 control groups. IMA level was measured using rapid colorimetric analysis developed (albumin-cobalt binding test). IMAR was calculated. Results: Forty-two of the CHB cases were female and 38 were male (age range: 46.62 +/- 2.69). Thirty of the HBI patients were female and 20 were male (age range: 40.83 +/- 3.71). Ten of the cases with CHC were female, and 20 were male (age range: 41.35 +/- 3.58). Thirty-three of the control group were female and 27 were male (age range: 30.45 +/- 1.08). Serum IMA levels and IMAR, CHB, HBI, and CHC cases were statistically significantly higher than the control group (p<0.05). However, in terms of IMA, IMAR, no statistically significant difference was found in the between CHB, HBI and CHC cases. In CHB and CHC, IMA and IMAR were statistically significantly higher in those with significant fibrosis than those with mild fibrosis (p<0.05). Conclusion: IMA and IMAR can be used as a marker in determining prognosis as an indicator of oxidative liver damage and in the evaluation of fibrosis (especially early detection of fibrosis).
Kronik Hepatit B ve C'de İskemi Modifiye Albüminin Önemi
Keywords: Chronic hepatitis B; HBeAg negative chronic infection; chronic hepatitis C; ischemia modified albumin; ischemia modified albumin; albumin ratio